COVID-19 and people management: The view of human resource managers - Sónia P. Gonçalves; Joana Vieira dos Santos; Isabel S. Silva; Ana Veloso; Catarina Brand\~ao; Rita Moura (Administrative Sciences, 2021)
COVID-19 has brought an unexpected need for change within organizations, particularly regarding human resource management. The nature of this global crisis has meant that these processes remain under-systematized. The aim of this study, which uses an exploratory design and mixed-methods analysis, is to contribute to describing the changes in human resource management practices and processes that resulted from this pandemic and to present the outlook of human resource managers for the future. One hundred and thirty-six Portuguese companies participated in the study, with the answers provided by their human resource managers. Results show that the main changes have occurred in the processes of work and safety, training, work organization, recruitment and selection, induction and onboarding, and communication. The profiles that emerged showed an association between the level of change and size of the organization. There was an increase in the use of teleworking and layoffs, and a positive assessment of the organizations' level of preparation and adaptation to this crisis. Human resource managers reported that the most evident changes in the future will be associated with the use of technology, teleworking, and work organization. These findings are of the upmost importance, as human resource managers are essential pillars in the adjustment of the organizations to this pandemic situation.
Keywords: 350; adaptation; challenges; changes; COVID-19; human resource management; layoff; organizations; preparation; teleworking